A Comprehensive Review of Solid Waste Management in Indian Cities: Challenges, Policies, and Sustainable Solutions - Mrs. Supriya Prasad Patil (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
India is facing a growing waste management crisis due to rapid urbanization and increasing waste generation. Many cities struggle with inefficient waste collection, lack of proper segregation, overflowing landfills, and weak enforcement of waste management policies. Although government programs like the Swachh Bharat Mission and Extended Producer Responsibility rules aim to improve the situation, challenges remain in infrastructure, funding, and public awareness. This paper examines the current state of waste management in India, the major challenges it faces, and the environmental, health, and economic impacts of improper waste disposal. It also explores innovative solutions such as smart waste collection systems, waste-to-energy projects, and decentralized waste processing, which can help improve efficiency. Additionally, the role of different stakeholders—including government agencies, private companies, NGOs, and informal waste workers—is discussed to understand how their efforts can contribute to better waste management. For India to tackle its waste problem effectively, a collaborative and technology-driven approach is needed. Strengthening policies, recognizing the contributions of informal waste workers, increasing investment in sustainable solutions, and encouraging public participation will be key to creating a cleaner and healthier future.
Keywords: Solid Waste Management; Waste Segregation; Sustainable Waste Solutions; Government Policies; Waste-to-Energy